(untitled) (European Journal of Pure and Applied Mathematics, 2024)
This paper presents the development of ε-Lukasiewicz fuzzy sets using the Lukasiewicz t-norm derived from a given fuzzy set. These ε-Lukasiewicz fuzzy sets are subsequently applied to UP (BCC)-algebras. In addition, the paper introduces the concept of ε-Lukasiewicz fuzzy UP (BCC)-ideals and examines their various properties. Three specific subsets, termed the -set, q-set, and O-set, are constructed, with an exploration of the conditions under which these subsets qualify as UP (BCC)-ideals.